Model Pembelajaran Make A Match dan Mufradat: Pengaruhnya terhadap Kontrol Mufradat Siswa - Ferantika, Susi; Jumhana, Nana; Faroji, Ahmad (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
This research is aims to determine the effect of using the Make A Match Technique which can increase Arabic vocabulary Control in class VII students of MTs Al-Khairiyah Karangtengah Cilegon Banten. Researchers used the experimental method with a quasi-experimental design. The data collection methods used in this study consisted of interview, documentation, observation and test. This study concluded that the use of the Make A Match technique had an impact on the Arabic vocabulary Control of class VII students of Mts Al-Khairiyah Karangtengah Cilegon Banten. This shows that the value (Tcount) 3.845 is greater than the value (Ttable) 2.064, so that Ho is rejected and H1 is accepted. In the sense that teaching Arabic using the Make A Match technique greatly influences students' ability to master Arabic vocabulary.